Um enfoque sócio-histórico do processo de ensino e de aprendizagem do conceito de energia mecânica - PUREZA, Odifax Quaresma (2004)
I want, in this study, to identify, in the explanations built from the classroom interactions, elements that show the way the students build the mechanic energy's concept and its forms, in the social and historical theory's point of view, observing, if the teaching and learning procces, provided an evolution of the student's ideas related to this topic. The answers provided by the students to the questions of a pretest were organized in categorys and compared, after the teaching and learning procces, with the answers provided in a post-test. Similar to the pretest, in order to identify, if there was or not, evolution of the ideas initialy presented by the students. The teaching and learning procces analysed, happened in a physics classroom from the 1st grade of the medium teaching, where participated a teacher and thirtyfive students. Was selected to analysis, a class recorded on video cassete tapes and on a micro cassete tapes, where was used as a selection rule of the episodes, the way that each group built, in the interaction with the teacher, the answer to the following question: in which type of energy, the mechanic energy associated to the sphere in the point A of a sloping plain, would turn into when it arrive at the point B in the same plain. A microgenetic analysis of the interactions and production of meanings occured in the classroom was made, where we try to make evident, the teacher's purpose, the discuss content, the comunicative approach, the standard of interactions and the forms of the teacher's interventions, in accord with the categories suggested by mortimer ans Scott (2002). This Analysis made evident the importance of the interactions in knowledge build, where the teacher made use of a comunicative approach interactive dialogic, but essentialy, of a comunicative approach interactive of authority. The standard of interactions made were, in some moments, of the type I - R - A, in another moments, of the type I - R - F - R ..., or still, of the type I - R - P - R .... The Teacher's Purposes during his intervenctions were sometimes in order to explore the Students's view and the understanding about specific ideas or phenomena, and sometimes to introduce or develop the scientific story, when making the scientific ideas available in the classroom social plan, or still, in order to guide and to keep the students's narrative in the way of this story's building. The teacher's pedagogic interventions forms, varied between give a shape to the meanings imputed by the students or to check their understanding about the meanings imputed in specific situations, or still, to mark key meanings, important to the building of the wanted explanation,as well as, to see the scientific story progress again. The interactions between the teacher and the students created a discuss in the classroom plan, xii which content propitiate that the students could build, to the situation in question, explanations guided by theory, because, those explanations always happened supported by a theoretic model that gaves them a sustentations to their elaborations. When comparing the pretest and the post-test results through the categories proposed in this study, it was made evident that, from the twelve-nine(29) students that took part in both, the pre and the post-test, twelve(20) showed an evolution in the thinking way and nine (9) kept themselves in the same category that they were classified by the pretest. From these, one (1) Already showed, by the pretest a way of thinking correspondent to the C5 category, which correspond to a more elaborated Thought about the mechanic energy topic and its forms, in a way that makes impossible to show in post-test na evolution in the way of thinking about this topic.